Evaluation of colour properties due to switching behaviour of a PDLC glazing for adaptive building integration. (May 2018) - Ghosh, A.; Mallick, T.K.
Abstract: In this study, intermediate transmissions, colour-rendering index (CRI) and correlated colour temperature (CCT) of an electrically actuated, switchable polymer dispersed liquid crystal (PDLC) glazing have been investigated. This 0.03 m 2 PDLC glazing changes its state from translucent to transparent in the presence of a 20 V AC power supply. Modulation of visible and NIR transmissions were observed for different applied voltages and no modulation was found in the UV range. For this particular type PDLC glazing, the CCT and CRI varied between 5430 K and 6100 K and 93 to 98, while luminous transmittance varied from 0.27 to 0.71 respectively. Low contrast ratio between the translucent and transparent states of this PDLC glazing offered a strong linear correlation between CCT and CRI. Highlights: Intermediate switching states were investigated for PDLC glazing. Variable solar factor was calculated for different solar transmission. Colour properties were calculated for variable transparent PDLC glazing.